Accident analysis of tungsten target coupled with ADS core. (11th May 2016) - Peng, Tianji; Lang, Minggang; Zhou, Zhiwei; Gu, Long
Abstract: The Accelerator Driven Subcritical Reactor System (ADS) is a kind of nuclear reactor which can burn minor actinide waste produced from conventional reactors with inherent safety features. Because of the characteristics of a sub-critical reaction process, the fission chain reaction is maintained by additional neutrons generated by protons in spallation target. This paper presents a concept design and the accident analysis of helium gas-cooled tungsten target for 10 MW helium-cooled experimental ADS. The thermal-hydraulic model of the target coupling with core was built, in which the solid domain was simulated with three-dimensional heat conduction model and the fluid domain was simulated with one-dimensional quasi-static model. In order to analyze the transient characteristics of the target with cooling system, a RELAP5-TRCAP coupling model for cooling system was established, in which the decay heat of the target and core was considered. The simulated results indicate that the peak temperature in the target is lower than the limiting value under the rated operation state and during four typical transient with actuation of the safety system. Highlights: A concept design of helium gas-cooled tungsten target for ADS is presented. A target-reactor coupling thermal-hydraulic code TRCAP for ADS was developed and coupled with RELAP5. The results demonstrate the effectiveness of transient model and the safety margin of target. The results of accident transients demonstrate the key factors for the target safety.